Exploring the Orthogonal Chemoselectivity of 2,4,6-Trichloro-1,3,5-Triazine (TCT) as a Trifunctional Linker With Different Nucleophiles: Rules of the Game - Sharma, Anamika; El-Faham, Ayman; de la Torre, Beatriz G.; Albericio, Fernando (Frontiers in Chemistry, 2018)
The study involves exploring the three orthogonal sites for aromatic nucleophilic substitution in cyanuric chloride (TCT). The preferential order of incorporation of different nucleophiles (such as alcohol, thiol, and amine) was addressed both experimentally and theoretically. The preferential order for incorporating nucleophiles in TCT was found to be alcohol > thiol > amine.